2010
DOI: 10.5424/sjar/2010082-1191
|View full text |Cite
|
Sign up to set email alerts
|

Low cost fish feed for aquarium fish: a test case using Colisa fasciata

Abstract: A comprehensive trial was undertaken to assess the effect of various types of feed on biomass conversion rate as well as on gonad (ovarian) weight in Colisa fasciata, a dual-purpose fish for food and ornamental use. Three groups of juvenile fish (3.0±0.015 g; 10.00±0.75 mm) were fed with three different types of feed: dried earthworm feed, laboratory prepared feed (LPF) and market feed. The LPF made with dried earthworm powder, eggshell powder and plant rhizome (Commelina sp.) dusts proved to be the best and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…As more assimilated energy is required for gonadal development, the ¢sh is left with minimum energy for growth and has also been reported in ornamental ¢sh like Colisa sp. (Chakrabarty, Das & Das 2008). Townshend and Wooton (1984) in their study reported that females allocated a higher proportion of food energy for gonadal development than the males.…”
Section: Discussionmentioning
confidence: 95%
“…As more assimilated energy is required for gonadal development, the ¢sh is left with minimum energy for growth and has also been reported in ornamental ¢sh like Colisa sp. (Chakrabarty, Das & Das 2008). Townshend and Wooton (1984) in their study reported that females allocated a higher proportion of food energy for gonadal development than the males.…”
Section: Discussionmentioning
confidence: 95%
“…), striped gourami ( Colisa fasciatus ) (Chakrabarty et al . ; Shafaet Hossen et al . ), can be reared either as food fish or as ornamental, therefore, conventional feeds can be used for ornamental scope.…”
Section: Ornamental Fish and Food Fish Feed Prices: Where Is The Gap?mentioning
confidence: 98%
“…From the economic point of view, this fact is easily expectable: the current production costs of ornamental fish are absolutely not compatible with ornamental fish feeds prices. Moreover, some fish species as sturgeons, crucian carp (Carassius carassius), iridescent shark (Pangasius hypophthalmus) (Hoseini et al 2015), albinic wels catfish (Silurus glanis) (Zatkova et al 2011), striped gourami (Colisa fasciatus) (Chakrabarty et al 2010;Shafaet Hossen et al 2014), can be reared either as food fish or as ornamental, therefore, conventional feeds can be used for ornamental scope. Taking into consideration these basic notions of ornamental fish farming management, it is clear that the difference in prices have not scientific reason to exist.…”
Section: Introduction To Artificial Feeding In Ornamental Aquaculturementioning
confidence: 99%
“…In developing countries by using fertilizer and commercial aqua feed in semi intensive sytem give low cost fish production Commercial aquafeed along with fertilizer give high fish yields, maximum growth and survival rate in ponds then fertilization alone (Chakrabarty and Das, 2008). Fish feed with more protein provide high growth and yield as compared to that provided with low crude protein (Razvi, 2006).…”
Section: Introductionmentioning
confidence: 99%